The Effect of Tourism Activities in Gili Islands Towards Students’ Speaking Skills at The Twelfth Grade of SMK Dane Rahil Lenek - Mul Muliadi; Ary Rahmat Hariadi; Samsul Rizal; Muh Roni Hidayatullah (Journal of Classroom Action Research, 2022)
Abstract: This research was conducted in response to the fact that most students at SMK Dane Rahil’s Tourism Department didn’t have proper English-speaking skills to work in tourism industry. Hence, the aimed this research: (1) to find out whether there are significant effects of tourism activities in the Gili Islands towards students’ speaking skills in the twelfth grade of SMK Dane Rahil Lenek; (2) to find out how tourism activities in Gili Islands affected students’ speaking skills in the twelfth grade of SMK Dane Rahil Lenek.This research used a pre-experimental design with one group pretest-posttest with purposive sampling technique. The treatment provided was internship programs in Gili Islands. The subjects of research were students of the twelfth grade of SMK Dane Rahil Lenek from tourism department. They were 24 students in total. It was conducted from December 2021 to March 2022. Tests and questionnaire were used as instruments. The SPSS 26 for Windows was used for analysis. The pretest cumulative average score was 2.9, minimum score was 2.4 and maximum was 3.4. It indicated that students’ speaking skills are poor. After the treatment, students were post tested with the results that cumulative average score was 4.2, minimum score was 3.6 and maximum was 4.8. It showed that tourism activities had significant effects towards students’ speaking skills. Whereas questionnaire results showed that students’ intense participation within activities had made them speak English frequently and improved their speaking skills significantly